(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article describes the formation, development and importance of academic mobility in the education system. Here the author dwells in detail on the works of the founders of the concept of the origin of academic mobility and analyzes the theoretical developments on it. It is emphasized that academic mobility is an effective technology in the successful integration of a country’s education system into global educational processes